2022
DOI: 10.3390/ijms232314939
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Search for Potential Biomarkers in Osteosarcoma: State-of-the-Art and Translational Expectations

Abstract: Osteosarcoma represents a rare cause of cancer in the general population, accounting for <1% of malignant neoplasms globally. Nonetheless, it represents the main cause of malignant bone neoplasm in children, adolescents and young adults under 20 years of age. It also presents another peak of incidence in people over 50 years of age and is associated with rheumatic diseases. Numerous environmental risk factors, such as bone diseases, genetics and a history of previous neoplasms, have been widely described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The chromosomal rearrangement of anaplastic lymphoma kinase (ALK) was first described in 2007 in anaplastic large cell lymphomas, and Soda et al reported that it occurs in ~7% of patients with NSCLC [ 68 ]. It is much more frequent in adenocarcinomas than in squamous or large cell tumors, where its presence is very rare [ 69 ].…”
Section: Targeted Therapy In Nsclcmentioning
confidence: 99%
“…The chromosomal rearrangement of anaplastic lymphoma kinase (ALK) was first described in 2007 in anaplastic large cell lymphomas, and Soda et al reported that it occurs in ~7% of patients with NSCLC [ 68 ]. It is much more frequent in adenocarcinomas than in squamous or large cell tumors, where its presence is very rare [ 69 ].…”
Section: Targeted Therapy In Nsclcmentioning
confidence: 99%
“…In Table 1 , we summarize the main miRNAs altered in the cell cycle and the type of cancer in which they appear. Because of this, an increasing number of works are studying their potential applications as translational biomarkers for use in prognosis or as predictive responses to the therapy received, as well as possible therapeutic targets to improve the clinical management of these patients [ 38 , 47 ].…”
Section: Role Of Micrornas In Cell Cyclementioning
confidence: 99%
“…As cells inside the bone begin to divide uncontrollably, osteosarcoma occurs and can be extremely aggressive and has distal metastatic properties. 5,6 Apoptosis, autophagy, necrosis, and pyroptosis are regular forms of cell death. 7 Ferroptosis, a new form of cell death, is mediated by intracellular iron and is clearly distinguished from other forms of cell death forms.…”
Section: Introductionmentioning
confidence: 99%